Sacred Outreach: The Infrastructure of Port Sanctuaries in Republican Latium - Moser, Claudia (Religion in the Roman empire, 2019)
By examining three sites which combined a religious sanctuary and access to a port, this paper reflects on the shared characteristics of connectivity and interface represented by religious and trade spaces, and on how they interpenetrate through artisan production, human frequentation and ritual behaviour, and urban development. The three sites of Ostia, Lavinium, and Satricum, two on the coast and one connected to a river, offer a case study in the inseparability of religious behaviour, economic activity, and geographical niche.